ASIAN THINK TANKS: GLOBAL ROLE AND IMPACT ON FOREIGN POLICY - K. R. Voda (Сравнительная политика, 2018)
The articles looks at the trends in the development of think tanks in major Asian countries. It reviews the posture of the Asian think tanks in global ratings. It also looks at the literature on think tanks in theUSA, western and Asian countries. Despite the fact that the first think tanks appeared inAsiain the 1950’s, they did not turn into a politically significant force. The reasons are insufficient financial independence and shortage of skills. Asian think tanks are often preoccupied with research for corporations and government agencies that provide their funding. It negatively affects the ability of the think tanks to independently set the research agenda and express critical viewpoint. However, think tanks often provide valuable platforms for dialogue among experts that can be helpful during periods of deterioration of the political relations between countries. For instance, the role of Japanese and Russian think tanks as “track two” diplomacy actors was helpful particularly during the period of deterioration of Russia-Japan relations in 2014-2015. The article also looks at the development of the Asian think tank networks. Most of these networks were created in support of regional frameworks such as APEC, ASEAN Plus Three, ARF, etc. Asian think tank networks depend on a number of “core institutions” that regularly host events and ensure continuity of the agenda. The article then draws conclusions on the potential ofRussia’s influence on ideological and political processes in the Asia-Pacific region.